Low Cytoplasmic Magnesium Increases the Specificity of the Lon and ClpAP Proteases - Yeom, Jinki (J Bacteriol, 2021)
Proteolysis is a fundamental property of all living cells. In the bacterium Salmonella enterica serovar Typhimurium, the HspQ protein controls the specificities of the Lon and ClpAP proteases. Upon acetylation, HspQ stops being a Lon substrate and no longer enhances proteolysis of the Lon substrate Hha. The accumulated HspQ protein binds to the protease adaptor ClpS, hindering proteolysis of ClpS-dependent substrates of ClpAP, such as Oat, a promoter of antibiotic persistence. HspQ is acetylated by the protein acetyltransferase Pat from acetyl coenzyme A (acetyl-CoA) bound to the acetyl-CoA binding protein Qad. We now report that low cytoplasmic Mg(2+) promotes qad expression, which protects substrates of Lon and ClpSAP by increasing HspQ amounts. The qad promoter is activated by PhoP, a regulatory protein highly activated in low cytoplasmic Mg(2+) that also represses clpS transcription. Both the qad gene and PhoP repression of the clpS promoter are necessary for antibiotic persistence. PhoP also promotes qad transcription in Escherichia coli, which shares a similar PhoP box in the qad promoter region with S. Typhimurium, Salmonella bongori, and Enterobacter cloacae. Our findings identify cytoplasmic Mg(2+) and the PhoP protein as critical regulators of protease specificity in multiple enteric bacteria. IMPORTANCE The bacterium Salmonella enterica serovar Typhimurium narrows down the spectrum of substrates degraded by the proteases Lon and ClpAP in response to low cytoplasmic Mg(2+), a condition that decreases protein synthesis. This control is exerted by PhoP, a transcriptional regulator activated in low cytoplasmic Mg(2+) that governs proteostasis and is conserved in enteric bacteria. The uncovered mechanism enables bacteria to control the abundance of preexisting proteins.